Optimizing Adjuvant Stereotactic Radiotherapy of Motor-Eloquent Brain Metastases: Sparing the nTMS-Defined Motor Cortex and the Hippocampus - Dzierma, Yvonne; Schuermann, Michaela; Melchior, Patrick; Nuesken, Frank; Oertel, Joachim; Rübe, Christian; Hendrix, Philipp (Frontiers in Oncology, 2021)
Brain metastases can effectively be treated with surgical resection and adjuvant stereotactic radiotherapy (SRT). Navigated transcranial magnetic stimulation (nTMS) has been used to non-invasively map the motor cortex prior to surgery of motor eloquent brain lesions. To date, few studies have reported the integration of such motor maps into radiotherapy planning. The hippocampus has been identified as an additional critical structure of radiation-induced deficits. The aim of this study is to assess the feasibility of selective dose reduction to both the nTMS-based motor cortex and the hippocampi in SRT of motor-eloquent brain metastases. Patients with motor-eloquent brain metastases undergoing surgical resection and adjuvant SRT between 07/2014 and 12/2018 were retrospectively analyzed. The radiotherapy treatment plans were retrieved from the treatment planning system (“original” plan). For each case, two intensity-modulated treatment plans were created: the “motor” plan aimed to reduce the dose to the motor cortex, the “motor & hipp” plan additionally reduce the dose to the hippocampus. The optimized plans were compared with the “original” plan regarding plan quality, planning target volume (PTV) coverage, and sparing of organs at risk (OAR). 69 plans were analysed, all of which were clinically acceptable with no significant differences for PTV coverage. All OAR were protected according to standard protocols. Sparing of the nTMS motor map was feasible: mean dose 9.66±5.97 Gy (original) to 6.32±3.60 Gy (motor) and 6.49±3.78 Gy (motor & hipp), p<0.001. In the “motor & hipp” plan, dose to the ipsilateral hippocampi could be significantly reduced (max 1.78±1.44 Gy vs 2.49±1.87 Gy in “original”, p = 0.003; mean 1.01±0.92 Gy vs. 1.32±1.07 Gy in “original”, p = 0.007). The study confirms the results from previous studies that inclusion of nTMS motor information into radiotherapy treatment planning is possible with a relatively straightforward workflow and can achieve reduced doses to the nTMS-defined motor area without compromising PTV coverage. Furthermore, we demonstrate the feasibility of selective dose reduction to the hippocampus at the same time. The clinical significance of these optimized plans yet remains to be determined. However, with no apparent disadvantages these optimized plans call for further and broader exploration.